Analisis Populasi Ikan Louhan (Cichlasoma x Paraneetroplus x Amphilophus) di Waduk Sempor, Kabupaten Kebumen - Muh. Sulaiman Dadiono; Pratiwi Restu Murti (Clarias : Jurnal Perikanan Air Tawar, 2023)
Flowerhorn fish (Cichlasoma x Paraneetroplus x Amphilophus) are dangerous to the local ecosystem of Indonesian waters. It is feared that the existence of flowerhorn fish in local waters will become the dominant predator. Based on this study, it is reported that catches of flowerhorn fish in the Sempor Reservoir, Kebumen Regency, Central Java have the potential to become invasive predatory fish. The research method uses the desk study method and field observations by informants. The flowerhorn fish caught in the Sempor Reservoir is a record for efforts to protect the natural ecosystem of the reservoir from invasion by foreign predatory fish. The existence of flowerhorn fish in the Sempor Reservoir must be monitored, mapped and regulated with strict rules so that the balance of the Sempor Reservoir ecosystem is maintained from foreign predatory fish.